Factors influencing intention for reusing virtual reality (VR) at theme parks: the mediating role of visitors satisfaction - Mohammad Nurul Alam; Jamshid Ali Turi; Abul Bashar Bhuiyan; Sami Al Kharusi; Michael Oyenuga; Norhayah Zulkifli; Juman Iqbal (Cogent Social Sciences, 2024)
This paper investigates the factors that influence visitors’ intention to reuse virtual reality (VR) in theme parks in Malaysia, specifically focusing on perceived usefulness, perceived ease of use, enjoyment, and compatibility, as well as the mediating role of visitor satisfaction. A field survey was conducted with 357 visitors using a quantitative research design, and the collected data was analyzed using SPSS and Smart-PLS software. The results indicate that perceived ease of use, enjoyment, and compatibility positively influence visitors’ intention to reuse VR, while visitors’ satisfaction mediates the relationship between perceived ease of use, compatibility, and intention to reuse VR. The study recommends that park owners and administrators ensure customers’ ease of use of VR and create innovative ideas and materials to enhance enjoyment, as retaining old customers is more feasible and less expensive than acquiring new ones. The study’s limitations include a small sample size and limited geographic scope, suggesting the need for future research to increase generalizability and incorporate variables such as subjective norms. Theme park managers can use the study’s findings to incorporate VR technology into their roller coasters and create a variety of VR experiences for visitors. Overall, the study advances theoretical understanding of related constructs and offers practical insights for theme park management.